Molecular basis for loss of virulence in Magnaporthe oryzae strain AM16 - Deng, Jiahui; Zhang, Ziya; Wang, Xingli; Cao, Yongni; Huang, Huichuan; Wang, Mo; Luo, Qiong (Frontiers in Plant Science, 2024)
The rapid virulence variation of Magnaporthe oryzae (M. oryzae) to rice is a big challenge for rice blast control. Even though many studies have been done by scientists all over the world, the mechanism of virulence variation in M. oryzae remains elusive. AM16, an avirulent M. oryzae strain reported in our previous study, provides an excellent entry point to explore the mechanism of virulence variation in M. oryzae. In this study, we found that the Pmk1 and Mac1 had specific mutations in strain AM16. The AM16 strains overexpressing Pmk1Guy11 or (and) Mac1Guy11 allele from strain Guy11 displayed significantly increasing conidiation, functional appressorium formation, and restoring pathogenicity to rice. Moreover, we observed that the strains overexpressing Mac1Guy11 had stronger conidia forming capacity than that of the strains overexpressing Pmk1Guy11, while the appressorium formation rate of strains overexpressing Pmk1Guy11 was similar to that of strains overexpressing Pmk1Guy11-Mac1Guy11, much higher than that of the strains overexpressing Mac1Guy11. Taken together, our results reveal that the natural mutation of Pmk1 and Mac1 genes are important, but not the sole cause, for the loss of virulence in strain AM16. The functional difference between Pmk1 and Mac1 in the growth and development of M. oryzae was first discovered, providing new insight into the pathogenic mechanism of M. oryzae.